The Development of A Nursing Supervision Model to Improve the Quality of Nursing in Critical Care - Chaiyasak, kanyaporn; Thongchip, Prakob; Thepchana, Netenapa; Pinsuwan, Onuma; Samerpop, Khattiya; Chaikate, Kuntalee (Princess of Naradhiwas University Journal, 2025)
This research and development aimed to develop a nursing supervision model to improve the quality of nursing in critical care and assess the outcomes of utilizing the model. Samples were 90 participants including the head nurse, the vice head nurse, and nurses with experience caring for critically ill patients and 100 clients who used Saun Hospital’s services. There were three phases of the research methodology: 1) Study nurse supervision issues; 2) Create a model for nursing supervision; and 3) Test and assess the results of using a model. The following were the research tools: 1) three parts of a nursing supervision model that the researcher developed, including the manual guidelines of a nursing supervision model, the adult learning program, and the practicum manual of critical care; 2) questionnaires that the researchers developed were validated by three experts with indexes equaled to 0.93, 0.93, 0.95, 0.8, and 0.7 and relied values equaled to 0.96, 0.96, 0.93, 0.93, and 0.93. The findings showed that: 1) the average scores of service quality and client satisfaction were at a high level; 2) the average scores of client opinion and contentment with a nursing supervision model were at a high level. The average knowledge score was statistically significantly higher after using the model than it was before; 3) nursing administration outcomes, nursing quality, sleep duration, and guideline practice after using the model were all equaled with the clinical outcomes standard after using the model. The prevalence of ventilator-associated pneumonia, high-risk medication errors, pressure sores, and fewer unplanned extubation.